Nanoalloys Synthesis, Structure and Properties - Alloyeau, Damien; Mottet, Christine; Ricolleau, Christian (Engineering Materials,, 2012)
Bimetallic nanoparticles, also called nanoalloys, are at the heart of nanoscience because of their ability to tune together composition and size for specific purposes. By approaching both their physical and chemical properties, Nanoalloys: Synthesis, Structure & Properties provides a comprehensive reference to this research field in nanoscience by addressing the subject from both experimental and theoretical points of view, providing chapters across three main topics: •Growth and structural properties •Thermodynamics and electronic structure of nanoalloys •Magnetic, optic and catalytic properties The growth and elaboration processes which are the necessary and crucial part of any experimental approach are detailed in the first chapter. Three chapters are focused on the widely used characterization techniques sensitive to both the structural arrangements and chemistry of nanoalloys. The electronic structure of nanoalloys is described as a guide of useful concepts and theoretical tools.  Chapters covering thermodynamics begin with bulk alloys, going to nanoalloys via surfaces in order to describe chemical order/disorder, segregation and phase transitions in reduced dimension. Finally, the optical, magnetic and catalytic properties are discussed by focusing on nanoparticles formed with one element to track the modifications which occur when forming nanoalloys. The range and detail of Nanoalloys: Synthesis, Structure & Properties makes it an ideal resource for postgraduates and researchers working in the field of nanoscience looking to expand and support their knowledge of nanoalloys.